AJARAN-AJARAN TASAWUF DALAM SASTRA KITAB RIAYAH AL-HIMMAH KARYA SYEKH AHMAD RIFAI - Nasrudin Nasrudin (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
Literary works of classical (religious) books are works of literature covering many disciplines, such as theology, fiqh (jurisprudence), hadis, and mysticism (tasawuf). Mysticism takes an important part since there are many of its experts or Sufi who are able to deliver Islamic teaching in accordance to the different levels of understanding of the society. Many of their works were written in Arabic alphabetical system, but the languages are Javanese, Sundanese, and Malay. The presence of Syekh Ahmad Rifai has influenced the works of classical literature. One of his works is Riayah al-Himmah, which is written in Javanese language with Arabic alphabetical system and in the form of nazam. In the middle of reform of Islamic world, Syekh Ahmad Rifai gave a good contribution in the reform of tasawuf. His spirit to harmonize the teaching of tasawuf in order not in contrast with Islamic law (syariat) is obvious. He taught zuhud, ikhlas, sabar, tawakal, ridlo as good attitude of Sufi/Salik to have spiritful, progressive, and optimistic life, not a fatalistic and pessimistic one. Sastra kitab merupakan jenis sastra yang mencakup berbagai bidang seperti ilmu kalam, fiqh, hadis dan tasawuf. Tasawuf menjadi bagian penting karena banyak para ahli tasawuf atau sufi yang mampu menyampaikan ajaran-ajaran Islam yang disesuaikan dengan tingkat pemahaman masyarakat. Karya-karya yang mereka tulis banyak yang berhuruf arab sedangkan bahasanya adalah bahasa jawa, sunda dan melayu. Kehadiran Syekh Ahmad Rifai telah mewarnai hazanah karya sastra kitab di Jawa. Salah satu karyanya adalah Riayah al-Himmah. Kitab ini ditulis dengan bahasa jawa dan menggunakan huruf arab dan diuntai dalam bentuk nazam. Ditengah-tengah munculnya pembaharuan dalam dunia Islam Syekh Ahmad Rifai telah memberikan andil yang baik dalam kaitannya dengan pembaharuan di bidang tasawuf. Semangat beliau untuk menselaraskan ajaran-ajaran tasawuf agar tidak bertentangan dengan syariat Islam sangatlah jelas. Ia mengajarkan zuhud, ikhkas, sabar, tawakkal, ridho sebagai sifat terpuji bagi para sufi/salik agar mempunyai semangat hidup yang progresif dan optimis bukan fatalis dan pesimis.